Risk Factors Associated with Enteric Septicemia of Catfish on Mississippi Commercial Catfish Farms. Issue 2 (30th April 2014) - Cunningham, Fred L.; Jack, S. W.; Hardin, David; Wills, Robert W.
Abstract: A gram‐negative bacterium, Edwardsiella ictaluri, is the cause of enteric septicemia of catfish (ESC), which is one of the most prevalent bacterial diseases in farm‐raised catfish. The objective of this study was to identify risk factors associated with ESC mortalities and are reported by farm personnel. To identify risk factors a catfish management database was developed. The odds ratios (OR) of the final multivariable logistic regression model were: (1) volume of the pond (OR, 0.56), (2) interval from harvest until a mortality event (OR, 1.49), (3) interval from stocking until a mortality event (OR, 0.52), (4) nitrite measured within 14 d of a mortality (OR, 3.49), (5) total ammonia measured within 14 d of a mortality (OR, 20.48), and (6) sum of feed fed for 14 d prior to the disease outbreak (OR, 1.02), all of which were significantly ( P ≤ 0.05) associated with ESC occurrence. This study showed that some commonly recorded production variables were associated with ESC outbreaks and if monitored could help identify "at risk" ponds prior to disease outbreaks. Received September 18, 2013; accepted December 17, 2013